Characteristics of patients with difficult-to-treat rheumatoid arthritis in clinical practice. (3rd March 2021) - Takanashi, Satoshi; Kaneko, Yuko; Takeuchi, Tsutomu
Abstract: Objectives: The aim of this study was to investigate the clinical characteristics of patients with difficult-to-treat RA (D2T RA) and the usefulness of switching to drugs with different modes of action in real-world. Methods: We reviewed all consecutive patients with RA treated at Keio University Hospital between 2016 and 2017 with a definition of D2T RA. We analysed clinical characteristics and evaluated the usefulness of changing drugs according to mode of action. Results: Among 1709 patients with RA, 173 (10.1%) were D2T RA. The reason for the D2T RA was multi-drug resistance in 59 patients (34.1%), comorbidity in 17 (9.8%), and socio-economic reasons in 97 (56.1%). The multi-drug-resistance group had significantly higher tender joint count and evaluator global assessment than the other groups, despite receiving the most intensive treatment. The comorbidity group showed a significantly older age and higher rheumatic disease comorbidity index. Although changing the drug to another with a different mode of action was useful, the proportion of patients who achieved remission or low disease activity decreased as the number of switches increased. Conclusion: Of the patients with RA, 10.1% were still difficult to treat in clinical practice, despite intensive treatment. Their characteristics were distinct by the reasons of D2T RA, which suggests the need for a personalized approach to D2T RA.